Resultados tipo Bernstein em M2 x R - Silva, José Wilker de Lima (2007)
We will present a formula for the Laplacian function Θ = where f : Sigma ^ {n} → M^{n } × R is an embedding with codimension one, Sigma ^{n}is a two-sided surface, T is a conformal field in Sigma ^{n} × R en is a unit field normal to Sigma ^{n} in M^{n} × R. We will use this formula to obtain some Bernstein-like results in M2 × R.